An Exploration of How to Deal With Tardy and Undisciplined Students: The Counseling Teacher Guidance Paradigm - Nur Azizatul Haqiah; Naufa Amalia; Nur Azimah Usman; Nurasiah (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research examines the Counseling Guidance Teacher Paradigm of SMA Negeri 13 Jambi City in Overcoming Students who are Late and Undisciplined. This type of research is descriptive. The research subject was a population of 1 person, while the sample of this study was one guidance counseling teacher who was taken. Data were collected using interview techniques from documentation and interviews and then explained in detail from the data. The results of this study show that students violate the rules and need to be more disciplined with the three most important forms, namely the reprimand process (orally), the calling process (in writing), and the coaching process (accompanied by giving punishment).